SUB-ACUTE TOXICITY TEST OF RED GINGER EXTRACT (Zingiber officinale var. Rubrum) ON MICE (Mus musculus): UJI TOKSISITAS SUB-AKUT EKSTRAK JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP MENCIT (Mus musculus) - Sulistiawati Putu Dewi; Mochammad Taha Ma’ruf (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Red ginger (Zingiber officinale var. rubrum) is one of the herbal plants used as a wound healing drug because it contains high oleoresin and essential oil. Red ginger also has antioxidant, anti-inflammatory, and antibacterial properties that can strengthen the immune system and prevent infection. For the safety of using herbal plants, it is necessary to do a toxicity test. Subacute toxicity test is a test to detect toxic effects after administration of test preparations with repeated doses given orally to test animals for 28 days. Objectives: the aim of the study is to determine whether red ginger extract has a toxic effect on the liver of mice. Materials and Methods: This is a laboratory experimental study using in vivo laboratory experimental methods using The Post Test Only Control Group design with sample grouping using a Completely Randomized Design. The 25 mice were divided into 5 groups, namely group I as control, group II to group V given the test extract at doses of 100, 200, 400, and 800mg/KgBW with one oral administration. On day 28, the mice were autopsied, and histopathological observations of the liver were performed. The data obtained were analyzed using the Kruskall Wallis test and continued with the Mann Whitney U test. Results and Discussions: in the control group tended to be in normal conditions, in treatment P1 parenchymal degeneration occurred, in treatment P2 hydropic degeneration occurred, in 55 treatment P3 hydropic degeneration and necrosis occurred, while in treatment P4 necrosis occurred. Conclusions: Red ginger extract had a subacute toxic effect on the liver of mice at a dose of 400 mg/kg BW, which was a score of 3 (hydropic degeneration) and a dose of 800mg/kg BW showed a score of 4 (necrosis).